PEMERIKSAAN DAN PENYULUHAN KADAR KOLESTROL SEBAGAI PENCEGAHAN DINI HIPERTENSI, STROKE DAN ATHEROSCLEROTIC CARDIOVASCULAR DISEASE DI DESA SINDANGSARI KECAMATAN LEUWIGOONG KABUPATEN GARUT - Muhammad Hadi Sulhan; Gina Nafsa Mutmainna; Mamay (LP4M STIKes Karsa Husada Garut, 2021)
Increased levels of cholesterol in the blood are the main precusors associated with coroner's artery disease, sudden death syndrome and atherosclerosis. Atherosclerosis is a common disorder caused by fat, cholesterol, and calcium deposits in the lining of the arteries. The purpose of examination and cholesterol levels in Sindangsari Village, Leuwigoong Subdistrict, Garut Regency is: Knowing cholesterol levels in the community, Increasing public knowledge about the dangers and complications of high cholesterol levels, Providing knowledge General and specific symptoms when cholesterol levels in the blood are high, provide knowledge about handling when indicated high cholesterol levels, socialize a healthy lifestyle to the community for the prevention of high cholesterol levels, The implementation method used is the examination of cholesterol levels in the community and direct public education during the examination to the citizens, namely as many as 60 people. From this community service activity can be concluded, the extension and extension of cholesterol is very beneficial for the cisereuh village community. The information conveyed is better understood by the public because of communicative methods with the achievement of 86% understanding of the material provided and 14% less understanding of the material. The data obtained is more accurate in describing the condition of the cholesterol levels of the community Kp. Cisereuh Ds Sindangsari Kec Leuwigoong.